1998
DOI: 10.1094/phyto.1998.88.8.844
|View full text |Cite
|
Sign up to set email alerts
|

Description of the Bacterium Causing Blight of Leek as Pseudomonas syringae pv. porri (pv. nov.)

Abstract: Forty bacterial strains isolated from leek blight (Allium porrum) in France and other countries were studied by conventional biochemical methods, serological reactions, numerical taxonomy, DNA-DNA hybridization, and ice nucleation activity, as well as by pathogenicity on leek and other host plants. They were compared with reference strains of Pseudomonas, mainly pathotype strains of P. syringae pathovars and strains of P. syringae pv. syringae isolated from various host plants including onions. Leek strains so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 14 publications
2
19
1
Order By: Relevance
“…All Australian leek strains produced a brown diffusible pigment on TSBA and BUGä agar after 2 days, as did the known pv. porri strains, consistent with the observations of Samson et al (1998). The strain 61456 from leek derived from seed from Japan, 75520 from onion from Japan, and the pv.…”
Section: Isolation and Pathogenicity Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…All Australian leek strains produced a brown diffusible pigment on TSBA and BUGä agar after 2 days, as did the known pv. porri strains, consistent with the observations of Samson et al (1998). The strain 61456 from leek derived from seed from Japan, 75520 from onion from Japan, and the pv.…”
Section: Isolation and Pathogenicity Studiessupporting
confidence: 88%
“…Lelliot (1952) described a bacterial disease of leeks caused by a pseudomonad, later attributed to a strain of P. syringae by Hale (1975). Samson et al (1981) reported similar symptoms in France and published a description of this pathogen (Samson et al, 1998), naming it P. syringae pv. porri.…”
Section: Introductionmentioning
confidence: 99%
“…As outlined in Scheme 1, condensation of allyl 3, 8 (2) in the presence of a catalytic amount of TMSOTf gave allyl 2,3,…”
Section: Resultsmentioning
confidence: 99%
“…We also found that the herbicide could inhibit NFB related to γ-proteobacteria in this study. As we know, γ-proteobacteria are an important group in soil, contributing to soil nitrification, antimicrobial activity and many other functions (Bremner 1997;Samson et al 1998). Therefore, long-term chlorimuron-ethyl application clearly disturbs soil biological functions.…”
Section: Fig 2 Nitrification Potential (Np) Error Bars Standard Devmentioning
confidence: 99%